Transformasi Dakwah Live Streaming pada Masyarakat Urban di Kota Bandung - Irawan, Dede; Lukman, Dede; Imanuddin Effendi, Dudy (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2024)
This research aims to describe the dominant motives in the transformation of conventional da'wah to live streaming da'wah among da'wah activists. This research uses the case study method, namely a series of scientific activities carried out intensively, in detail and in depth about an event, to obtain in-depth knowledge about a specific event. The theories used include Max Weber's theory of social action and William F. Ogburn's theory of social change. The problem that is seen to arise is the loss of the intimate atmosphere in da'wah activities, because the use of digital media has eliminated the direct interactive aspects. Apart from that, the transformation of live streaming da'wah has given rise to a binary opposition from religion itself, instead of looking for alternatives so that da'wah can continue to be carried out, at the same time da'wah loses its sacredness.